METAPHOR AS AN IMAGE-BEARING STYLISTIC DEVICE (E Conference Zone, 2022)
It is true to state that the notion of image dates back to a long history. Ancient philosophers like Aristotle or Zizeron are considered to be the first to introduce this phenomenon in their works. Vinogradov V. V. (1963) provides the initial scientific identification of the notion of image in poems. [1, p133] They investigated imagery thoroughly and regarded it as an important aspect of stylistics. In the article we’ll try to investigate metaphor as one of the image -bearing stylistic device through analysis some examples taken from literary works of English writers.